An Analysis of Injury Trends and Disease Burden From Three Surveillance Hospitals in Urumqi From 2006 to 2018 - Zhang, Rong; Sun, Jing-Xuan; Guo, Ying-Zhen; Liu, Lai-Xin; Wushouer, Fuerhati; Dong, Yan; Fang, Ping; Muyiduli, Xiamusiye; Gao, Zhen-Guo; Dai, Jiang-Hong; Ni, Ming-Jian (Frontiers in Public Health, 2022)
Objective: To investigate injury trends, injury distribution, and disease burden from three surveillance hospitals in Urumqi from 2006–2018. Method: Injury data from the National Injury Surveillance System (NISS) from three hospitals in Urumqi (2006–2018) were collected to analyze changes in the characteristics of outpatient injury cases. Years of potential life lost (YPLL) were calculated to determine the disease burden of the injury cases. Results: A total of 161,400 injury cases were recorded over 13 years, and the average age of the patient seeking medical attention was 32.4 years old. Male patients outnumbered female patients with a ratio of 1.6:1, but the proportion of female patients was greater after 45 years of age. The highest number of cases occurred in patients 15–29 years of age, accounting for 26.8% of all injury cases. Injury in females occurred most frequently in the home. A total of 41.4% of injury cases occurred while doing housework. The top three causes of injury were falls (49.7%), blunt force of an object, (13.7%), and motor vehicle accidents (MVA) (13.5%). Years of potential life lost from injury accounted for 7.39% of the total YPLL in the three hospitals. Conclusion: Males should be targeted for injury prevention and intervention in Urumqi. The prevention of falls, blunt force of objects, and MVA should be made a priority. Injury prevention strategies and targeted projects should be developed to reduce the disease burden of injury.